Effect of sulfonation modification of polycarboxylate superplasticizer on tolerance enhancement in sulfate. (1st March 2021) - Guan, Jianan; Liu, Xiao; Lai, Guanghong; Luo, Qifeng; Qian, Shanshan; Zhan, Jiayu; Wang, Ziming; Cui, Suping
Graphical abstract: Highlights: A novel sulfonate-modified PCE was synthesized based on innovative molecular design. Sulfonate modification on the side chains of PCE can enhance the sulfate tolerance. Effects of competitive adsorption, ionic strength and conformation were studied. Good performance retention and stability were shown for solving compatibility problem. Many quantitative evaluation indexes for sulfate tolerance of PCE were established. Abstract: A novel polycarboxylate superplasticizer (PCE) was synthesized by graft copolymerization between acrylic acid (AA) and end-functionalized poly (allyl sulfonate) (PALS) to produce comb polymer, i.e. PAA-g-PALS. The molecular structure was confirmed by Infrared Spectroscopy (IR) and 1 H Nuclear Magnetic Resonance ( 1 H NMR), and the molecular properties were characterized by Gel Permeation Chromatography (GPC). The conventional PCE with comb structure using isobutenyl polyethylene glycol (IPEG) as side chains (i.e. PAA-g-IPEG) was also synthesized to explore the effect of the side chain on the PCE performances. The fluidity and its retention, rheological properties, hydrodynamic radii (Rh ), adsorption behavior and zeta potential of the cement pastes containing PAA-g-PALS or PAA-g-IPEG were comparatively tested. It was found that this designed "sulfonate modified PCE" exhibited stronger dispersing stability and sulfate tolerance to cement paste and less sensitive to the sulfate competitive adsorption and the increase in ionic strength. Based on the above results, the evaluation method (the sulfate resistance index of PAA-g-PALS was increased by 24% as compared to that of PAA-g-IPEG) was innovatively established and the mechanism of sulfate resistance was clarified in detail. The purpose of this research is to offer an avenue with great potentials to synthesize a novel PCE with excellent workability retention and sulfate tolerance in fresh cement pastes. This sulfonate-modified polycarboxylate superplasticizer has great potentials as a viable alternative to conventional PCE, especially in some harsh cement systems.